Dynamics of biometric indicators of energy willow plants depending on planting density and feeding background - N. L. ТКАCHUК (Передгірне та гірське землеробство і тваринництво, 2021)
Development of world civilization is closely linked to energy resources, which significantly affect the country's independency policy.